2005
DOI: 10.1128/jb.187.21.7176-7184.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Hypervariable 130-Kilobase Genomic Region of Magnetospirillum gryphiswaldense Comprises a Magnetosome Island Which Undergoes Frequent Rearrangements during Stationary Growth

Abstract: Genes involved in magnetite biomineralization are clustered in the genome of the magnetotactic bacterium Magnetospirillum gryphiswaldense. We analyzed a 482-kb genomic fragment, in which we identified an approximately 130-kb region representing a putative genomic "magnetosome island" (MAI). In addition to all known magnetosome genes, the MAI contains genes putatively involved in magnetosome biomineralization and numerous genes with unknown functions, as well as pseudogenes, and it is particularly rich in inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
294
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(302 citation statements)
references
References 45 publications
(49 reference statements)
4
294
1
3
Order By: Relevance
“…In addition, there was also the possibility of gene loss, for example, the loss of mam genes, which has been shown to occur in cultures of some magnetotactic bacteria that also lost the magnetotactic trait (Ullrich et al, 2005;Kolinko et al, 2011). This unique application of genomic sequencing and analysis of microbial environmental DNA contributed to the understanding of many physiological features involved in the behavior and multicellular life of Ca.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was also the possibility of gene loss, for example, the loss of mam genes, which has been shown to occur in cultures of some magnetotactic bacteria that also lost the magnetotactic trait (Ullrich et al, 2005;Kolinko et al, 2011). This unique application of genomic sequencing and analysis of microbial environmental DNA contributed to the understanding of many physiological features involved in the behavior and multicellular life of Ca.…”
Section: Discussionmentioning
confidence: 99%
“…gouldi represent one of the few described magnetotactic gammaproteobacteria (Simmons et al, 2004;Lefèvre et al, 2012;Wang et al, 2013). Genomic studies have shown that genes responsible for magnetosome formation are often organized within 'magnetosome islands' that contain mobile elements (Ullrich et al, 2005;Jogler et al, 2009), and recent work suggests a monophyletic origin for magnetotaxis within the proteobacteria (Lefèvre et al, 2013b). Inclusions resembling magnetosomes, but interpreted as viruses, have been noted in other thyasirid symbionts, notably in 'symbiont of Thyasira flexuosa 1' from the Mediterranean, in Figure 4; (Brissac et al, 2011), in symbionts of T. gouldi from Scotland (Southward and Southward, 1991) and of T. flexuosa from Long Beach, USA (Dufour, 2005) and Brest, France (J. Laurich, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…A spontaneous non-magnetic mutant that lacks the magnetosome island was also obtained with the M. gryphiswaldense MSR-1 strain (Schübbe et al 2003). Various phenotypes showing altered numbers, sizes and alignment of BacMPs were isolated and analysed (Ullrich et al 2005). The mutants revealed several deletions in different regions, suggesting the occurrence of frequent transposition events in the cell.…”
Section: Genome Analyses Of Magnetotactic Bacteriamentioning
confidence: 99%